Characterization of the whole plastome of Dipentodon Sinicus (Dipentodontaceae) - Changkun Liu; Lili Liu; Lei Jin; Zhenyan Yang; Yunheng Ji (Mitochondrial DNA. Part B. Resources, 2019)
In this study, we sequenced and assembled the whole plastome of Dipentodon sinicus. The plastome was 158,020 bp in length and consisted of a pair of inverted repeat regions (IRs, 26,551 bp), a large single-copy region (LSC, 86,624 bp) and a small single-copy region (SSC, 18,294 bp). It encoded 114 unique genes (80 protein-coding genes, 30 tRNA genes and 4 rRNA genes). Phylogenetic analysis showed that Dipentodon sinicus was sister to Tapiscia sinensis.